Analisis Penerapan Teknologi Augmented Reality (AR) Terhadap Hasil Belajar Siswa SMK Nusatama Padang Jurusan Akuntansi Sebagai Media Pembelajaran Interaktif - Harmelia, Harmelia; Putri, Yonna Anggayu; Seplinda, Mutia (Cetta: Jurnal Ilmu Pendidikan, 2025)
This study aims to analyze the application of Augmented Reality (AR) technology as an interactive learning medium and its impact on student learning outcomes at SMK Nusatama Padang majoring in Accounting. The background of this study is based on the importance of learning innovations that can improve the understanding of abstract accounting concepts through interactive visualization. The research method used was a quasi-experimental with a pretes-postes control group design. The research subjects consisted of two classes: the experimental class using AR media and the control class using conventional methods. Data were collected through learning outcome tests and analyzed using descriptive statistics and independent t-tests. The results of the study showed that there was a significant difference between the learning outcomes of students in the experimental class and the control class with an average post-test score of 77.4 for the experimental class or 80% of students categorized as having completed and an average for the control class of 63.28 or 40% of students categorized as having completed. These results showed that the average for the experimental class was higher than the class that did not use AR media. These findings indicate that the application of AR technology can effectively improve students' conceptual understanding and learning interest. In addition, the use of AR also provides a more engaging and immersive learning experience, which encourages active student involvement in the learning process. Based on these results, it can be concluded that AR technology is a potential alternative learning medium for application in vocational education, particularly in accounting learning. This study recommends the integration of AR into the curriculum and teacher training to optimize its use in the teaching and learning process.